Recreational mathematics in the development of creative thinking of Peruvian students of primary school (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In traditional schools, the creativity tasks were related to art and literature. People rarely think mathematicsprovides a fundamental space for them. This research’s objective is to determine the possible influence of the implementationof recreational mathematics on the development of creative thinking in university students. Through a quasi-experimentalresearch, some modules of recreational mathematics were applied to a population of 125 students in the control group andexperimental group. A random sampling was carried out, which allowed the constitution of a sample of 100 students that wereproportionally divided into an experimental group and a control group. These were assessed through a creativity test. Theresults show that 66 % of the students increased their level of creativity in contrast to the low results of the control group. Theuse of recreational mathematics turned out to be an important tool to improve the creative thinking of the students.